Prophecies of Language : the Confusion of Tongues in German Romanticism. - Mendicino, Kristina (Lit Z FUP., 2016)
Mendicino retraces the ways in which the task of translation is tied in Romantic writing to prophecy, not in the sense of telling future events, but in the sense of speaking in the place of another, such that language takes place in more than one voice--and tongue--at once, unpredictably.